Existence of Periodic Solutions for a Class of Asymptotically p-Linear Discrete Systems Involving p-Laplacian - Kai Chen; Qiongfen Zhang (Journal of Applied Mathematics)
By applying Mountain Pass Theorem in critical point theory, two existence results are obtained for the following asymptotically p-linear p-Laplacian discrete system Δ(|Δu(t−1)|p−2Δu(t−1))+∇[−K(t,u(t))+W(t,u(t))]=0. The results obtained generalize some known works.